2019
DOI: 10.1029/2019pa003721
|View full text |Cite
|
Sign up to set email alerts
|

Precessional Drivers of Late Miocene Mediterranean Sedimentary Sequences: African Summer Monsoon and Atlantic Winter Storm Tracks

Abstract: Cyclic sedimentary patterns in the marine record of the Mediterranean Sea have been consistently correlated with orbitally-driven shifts in climate. Freshwater input driven by the African summer monsoon is thought to be the main control of such hydrological changes, where the runoff signal is transferred from the eastern to the western Mediterranean. The geological record from the Atlantic margin also contains precession-driven dilution cycles that have been correlated with the sedimentary sequences in the wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…These relationships suggest that while fluvial inputs may have influenced seawater Pb isotope compositions, they are not responsible for the more radiogenic compositions at insolation minima. This is consistent with the relatively small changes in the hydrologic budget across precessional cycles expected for the Western Mediterranean (Marzocchi et al, ; Modestou et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These relationships suggest that while fluvial inputs may have influenced seawater Pb isotope compositions, they are not responsible for the more radiogenic compositions at insolation minima. This is consistent with the relatively small changes in the hydrologic budget across precessional cycles expected for the Western Mediterranean (Marzocchi et al, ; Modestou et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, there are significant differences in the temporal occurrence of several proxies between Mediterranean sub‐basins; for example, sapropels in the Western Mediterranean are often less distinct, spatially less extensive, and sometimes missing entirely in the Plio‐Pleistocene compared to the Eastern Mediterranean (Murat, ). The east‐west spatial discrepancy is due to the fact that the intense increase in monsoon‐driven runoff during insolation maxima is primarily channeled into the eastern basin (Marzocchi et al, ; Emeis, Struck, et al, ; Rossignol‐Strick, ), suggesting different processes are responsible for sapropel development in the west (Emeis, Struck, et al, ; Murat, ). Finally, substantial changes in salinity occurred in the Mediterranean during the Messinian Salinity Crisis (MSC; 5.971–5.333 Ma; Krijgsman et al, ; Lourens et al, ; Manzi et al, ), which obscured normal marine sedimentation and the biological activity moderating organic proxies altogether.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Goldner et al (2014a) for the early to middle Miocene, orbital changes were found to improve the model-data mismatch, although the improvement was small and localized. The role of orbital forcing in the late Miocene climate (8 Ma) has been investigated in three coupled climate model studies (Marzocchi et al, 2019(Marzocchi et al, , 2015D. Simon et al, 2017).…”
Section: Impact Of Orbit On Miocene Climatementioning
confidence: 99%
“…(2014a) for the early to middle Miocene, orbital changes were found to improve the model‐data mismatch, although the improvement was small and localized. The role of orbital forcing in the late Miocene climate (8 Ma) has been investigated in three coupled climate model studies (Marzocchi et al., 2019, 2015; D. Simon et al., 2017). They found that the orbital forcing does not change the mean global surface temperature greatly, but can have substantial regional impact on both precipitation and temperature.…”
Section: Climate Modeling Of the Miocenementioning
confidence: 99%
“…Northward latitudinal migrations of the Intertropical Convergence Zone (ITCZ) and intense monsoons in Africa and Asia have been related to large summer Nile discharges (Castañeda et al, 2016;Revel et al, 2010) and sapropel formation (Rohling & Hilgen, 1991;Rohling et al, 2015;Rossignol-Strick et al, 1982). Events of enhanced Nile discharge were also synchronous to periods of increase annual rainfall in the northern and southern Mediterranean catchment areas (Bar-Matthews et al, 2000;Toucanne, Minto'o, et al, 2015;Tzedakis, 2005;Tzedakis et al, 2002Tzedakis et al, , 2009Wagner et al, 2019;Zanchetta et al, 2007), showing the strong coupling between the low and midlatitude hydrological cycle (Bosmans et al, 2015(Bosmans et al, , 2020Kutzbach et al, 2014;Marzocchi et al, 2019). Our data thus confirms the strong link between precession minima, instense Asian and African monsoons, sapropels and weak MOW at Gibraltar.…”
Section: 1029/2020pa003931mentioning
confidence: 99%